The Management of a Community-Based English Language Course in the 21st Century: A Case Study of The Bale English Course, Central Lombok - Muhammad Isro' Hidayatullah; Rizka Sulisyana; Melinda Septiani; Lalu Mochamad Ridho Luthfi; Umi Sulvian; Maesri Latipah (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
Non-formal education plays a crucial role in developing 21st-century competencies, particularly in English language skills. This study aims to analyze the implementation and management of learning at the Bale English Course (BEC), a community-based non-formal education institution, in developing the English language skills of rural communities. Using a descriptive qualitative approach, data were collected through observation and in-depth interviews. The results show that the learning program at BEC includes class divisions based on ability, the use of participatory methods, the integration of 21st-century skills (4C), as well as support for contextual activities such as public speaking and social service. Obstacles faced include limited teaching staff and limited infrastructure. BEC plays a crucial role in developing English language skills, particularly in responding to 21st-century challenges through a communitybased approach and simple, contextual learning programs, while maintaining the continuity of learning activities with an inclusive approach. The implications of this study show the importance of policy support and strengthening institutional capacity for non-formal education in rural areas.